Wilde, Richard (audio interview #2 of 4) - Wilde, Richard (1920 - ); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This is the second of four interviews conducted in Wilde's office in the CSULB History Department. The audio quality is good, but there is some background noise as people talk as they pass by in the hall. 11/7/1980